Characterization and Optimization of Natural Maltodextrin-based Niosome - Nasrul Wathoni, Sriwidodo, Uray Camila Insani (Journal of Applied Pharmaceutical Science, 2013)
Natural maltodextrin, due to their outstanding merits, have received more and more attention in the field of drug delivery systems. In particular, maltodextrin seem to be the most promising materials in the preparation of niosome carriers. This study aimed to optimize and characterize the formulation of natural maltodextrin-based niosome. The natural maltodextrin was made from cilembu sweet potato starch which used partial starch hydrolysis method by α-amylase enzyme. Proniosome and niosome formulations used three various concentration of surfactant (sorbitan monostearat) which about 5 mmol, 7.5 mmol, and 10 mmol for formula 1 (F1), formula 2 (F2), and Formula 3 (F3) respectively. In addition, physical and chemical characterizations had been done to characterize maltodextrin, proniosome, and niosome. The Dextrose Equivalent (DE) value of natural maltodextrin was 7.99+0.11. Furthermore, the vesicle size of proniosome was in the range of 5µ to 13µ. The entrapment percentages of piroxicam in niosome formulations were 72.5+1.1%,, 76+1.7 %, and 77.5+1.9 % for FI, F2 and F3 respectively. It can be concluded that the result provided an indication of natural maltodextrin from Cilembu sweet potato starch are potentialy carrier in the proniosome preparation which can be used for producing niosomes.
Keywords: Piroxicam, Niosome, Maltodextrin, Cilembu Sweet Pota